ANALISIS IMPLEMENTASI KEBIJAKAN DESA BINAAN IMIGRASI DI KANTOR IMIGRASI KELAS I NON-TPI BOGOR - Annisa Tenri Rawesompa (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Immigration-Assisted Village Development Program is a preventive policy designed to enhance public awareness and participation through education on Non-Procedural Indonesian Migrant Workers (PMI NP) and the prevention of Trafficking in Persons (TPPO). However, the program has not yet undergone adequate assessment, resulting in unclear standards for measuring its success and effectiveness. This study aims to analyze the implementation of the Desa Binaan Imigrasi policy at the Bogor Immigration Office. This research employs a descriptive qualitative method with data collected through interviews, observations, and documentation involving six informants representing both internal immigration officials and external stakeholders. The findings show that the implementation of the program in Cisarua Village has generated positive impacts, including increased public understanding of immigration issues, greater community participation in reporting foreigners suspected of violating immigration regulations, and strengthened preventive efforts against TPPO and non-procedural migration. Nonetheless, the implementation remains constrained by the absence of a dedicated budget allocation, causing the program to rely on funding from other operational activities. Based on these findings, this study recommends the establishment of a specific budget allocation, the implementation of regular quarterly socialization activities, and enhanced coordination with relevant stakeholders to support the effectiveness and sustainability of the program.